EVALUASI PROGRAM IRIGASI PERPOMPAAN DALAM MENINGKATKAN KETAHANAN PANGAN DI KABUPATEN TANA TORAJA - Idam Hanafi K; La Sumange; Herman Nursaman; Helda Ibrahim (Journal of Innovation Research and Knowledge, 2025)
This study aims to evaluate the effectiveness of the pump-based irrigation program in enhancing food security in Tana Toraja Regency, with a case study conducted in Mengkendek District. The research addresses three main issues: (1) the effectiveness of the implementation of the pump irrigation program, (2) the program’s contribution to food security in terms of availability, access, and stability, and (3) supporting and inhibiting factors influencing the program’s implementation. A qualitative descriptive method supported by quantitative data from a Likert-scale questionnaire was employed. A total of 21 farmers from seven farmer groups participated in the study. The findings indicate that the pump irrigation program is effective, with an average score of 4.02 (high category). The program contributes significantly to improving food availability and access, as reflected in increased production, income, and cropping intensity. Food stability also improved, although it remains affected by price fluctuations and uneven water distribution caused by the region’s topography. Key supporting factors include strong farmer participation, government support, and adequate water sources. Major constraints involve high operational costs, frequent pump damage, limited technical training, and mountainous terrain. The study concludes that pump-based irrigation plays an important role in strengthening food security, yet requires further technical and institutional optimization to ensure sustainability.